The Identities of Second-Generation Indonesian Diaspora Communities - Stümer, Dewicynthia (KnE Social Sciences, 2022)
Indonesian emigrants and their descendants are important actors in developing Indonesia and their new home countries. These diaspora members have advantages such as intercultural and language skills as well as networks for economic activities. Digitalization increases and accelerates the bilateral influence of this group on personal networks, economic contributions, knowledge transfer, and political engagement. This article draws from social identity theory and the culture cycle to explore the sense of belonging of second-generation Indonesian diaspora members in Germany. The aim is to understand how the relationship of the Indonesian diaspora changes due to birth and socialization in Germany and cross-cultural parenting. The findings of this thesis suggest that members of the second-generation Indonesian diaspora have a strong sense of cultural belonging to Indonesia and tend to separate themselves culturally from Germany. Keywords: social identity, diaspora, sense of belonging, model minority myth, culture and the self, Germany, Indonesia